AI-Generated Object: Is it a ‘Work’ and Who Owns it? - Grumulaitis, Artūras (Teisė, 2024)
The evolution of generative AI and the popularity of diffusion models have opened up new opportunities for creativity, but have also raised several legal challenges in the field of copyright. This concerns both the use of copyrighted works in databases for training algorithms and the legal protection of the generated results. The generation of new text, video, audio objects, software codes, and synthetic data is directly connected to the legal terminology, such as ‘author’, ‘work’, ‘originality’ and ‘copyright protection’. In practice, questions arise as to whether AI-generated creations meet the requirements of originality, who should be considered as the author of such an object, and so on.Therefore, the aim of this article is to assess the impact of the development of generative AI on today’s copyright law and to answer whether objects created by generative AI should be granted copyright protection. The paper assesses whether the objects created by generative AI are considered ‘work’ in the sense of the Lithuanian (EU) copyright law and discusses the current issues of the authorship and ownership of such objects.
Keywords: generative artificial intelligence; copyright; AI-generated object; originality; diffusion models; Midjourney; ChatGPT